The Role of the Right to Information Law in Combating Corruption in Nepal - Acharya, Chiranjivi (Journal of Rapti Babai Campus, 2025)
This article examines the vital role of the Right to Information (RTI) in addressing corruption in Nepal. As a fundamental right guaranteed by the Constitution, RTI empowers citizens to demand transparency and accountability from public institutions, which are crucial for democratic governance. The paper traces the historical development of RTI in Nepal, explores its legal frameworks, and highlights its potential as a powerful tool for exposing and curbing corruption. Through case studies, the article demonstrates how the effective implementation of RTI has contributed to reducing corruption in various government sectors. The conclusion underscores the importance of citizens actively utilizing RTI to promote good governance, reduce corruption, and foster democratic and sustainable development.